2022
DOI: 10.2147/ijn.s374895
|View full text |Cite
|
Sign up to set email alerts
|

Combined Shikonin-Loaded MPEG-PCL Micelles Inhibits Effective Transition of Endothelial-to-Mesenchymal Cells

Abstract: Introduction Shikonin is well known for its anti-inflammatory activity in cardiovascular diseases. However, the application of shikonin is limited by its low water solubility and poor bioavailability. Methoxy poly (ethylene glycol)-b-poly (ε-caprolactone) (MPEG-PCL) is considered a promising delivery system for hydrophobic drugs. Therefore, in this study, we prepared shikonin-loaded MPEG-PCL micelles and investigated their effect on endothelial-to-mesenchymal transition (EndMT) induced by inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Nowadays, with the development of novel drug delivery systems through the use of liposomes, nanoparticles, cyclodextrin complexes, microemulsions, nanogels, etc., the pharmaceutical innovation of shikonin is in progress with the improvement of shikonin-based drugs. It was observed that methoxy poly (ethylene glycol)-b-poly (ϵ-caprolactone) micelles significantly improved the endothelial-to-mesenchymal transition–inhibiting effect of free shikonin, which makes it suitable for development as a lipophilic drug carrier [ 44 ].…”
Section: Shikonin In Medicine and Pharmacymentioning
confidence: 99%
“…Nowadays, with the development of novel drug delivery systems through the use of liposomes, nanoparticles, cyclodextrin complexes, microemulsions, nanogels, etc., the pharmaceutical innovation of shikonin is in progress with the improvement of shikonin-based drugs. It was observed that methoxy poly (ethylene glycol)-b-poly (ϵ-caprolactone) micelles significantly improved the endothelial-to-mesenchymal transition–inhibiting effect of free shikonin, which makes it suitable for development as a lipophilic drug carrier [ 44 ].…”
Section: Shikonin In Medicine and Pharmacymentioning
confidence: 99%
“…Consequently, the use of micelles in oral formulations is gaining popularity [88]. Li et al [89] investigated the effect of methoxy polyethylene glycol-β-gathering (MPEG-PCL) micelles loaded with Shikonin on inflammatory cytokine-induced endothelial mesenchymal transition (EndMT). The experimental results demonstrated that MPEG-PCL micelles significantly enhanced the cellular absorption of Shikonin.…”
Section: New Dosage Forms Of Shikonin In Diseasesmentioning
confidence: 99%
“…On the other hand, the encapsulation of shikonin in nanoparticles coated with saponin and sophorolipid significantly improved its solubility and bioavailability [371]. In another research, shikonin was loaded to MPEG-PCL micelles (methoxy poly (ethylene glycol)-b-poly ( -caprolactone)) which effectively inhibited EMT in endothelial model cells [372].…”
Section: The Bioavailability and Safety Of Compounds Reviewedmentioning
confidence: 99%